Gender wage gap across the quantiles: What is the role of firm segregation? - Ezgi Kaya (Cardiff University, Cardiff Business School, 2019)
In this paper, we explore the role of firm segregation on the gender wage gap. Using linked employee-employer data for Turkey, we investigate whether female segregation into low-paying firms and into low-paying jobs within a firm influence the gender wage gap across the wage distribution. We find that there is a 'glass ceiling' effect in the Turkish labour market, but this effect is more apparent within a firm than between firms. We also find a 'sticky floor' effect, but only among workers employed at the same firm. Our results imply that the allocation of women into low-paying jobs within each firm accounts for the existence of these effects more than the segregation of women into low-paying firms.
Keywords: C21; J31; J71; 330; gender wage gap; segregation; within- and between-firms; glass ceiling; sticky floor